Late Occurring Ectopic Pregnancy in a Posthysterectomy Patient - Munazza Anis; Abid Irshad; Susan Ackerman (Case Reports in Obstetrics and Gynecology)
The incidence of ectopic pregnancy after hysterectomy is extremely rare with only 56 cases reported in the medical literature. Due to its rare occurrence, this diagnosis may not be initially considered when such a patient presents with abdominopelvic pain. It is an important diagnosis to keep in mind since a delay in diagnosis may lead to death. The case presented below describes this extremely unusual diagnosis of an ectopic pregnancy which occurred six years after a supracervical hysterectomy.